2001
DOI: 10.1177/019394590102300603
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors of Postpartum Depression in Diverse Groups of Women

Abstract: The purpose of this study was to test the extent to which a causal model developed from a theoretical formulation of postpartum depression was consistent with data collected from three groups of postpartum women. In this cross-sectional, correlational design, the samples consisted of primarily middle-class, Caucasian mothers of term infants and preterm infants, and low-income, African American mothers of term infants. Instruments included the CES-D Depression instrument, the Postpartum Support Questionnaire, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 26 publications
5
47
0
1
Order By: Relevance
“…The frequency of having someone available, if needed, for positive social interaction and emotional, tangible, affectionate, and instrumental support appears to have a protective effect on the risk of postpartum depression, consistent with the literature (Beck 2001;Logsdon and Usui 2001) and our theoretical model. Qualitative data from this study revealed that women reported sources of support to include mothers, husbands or partners, and older children, but for women who lack those resources, a primary care provider inquiring about the mothers' support and helping them identify community resources may be an option.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The frequency of having someone available, if needed, for positive social interaction and emotional, tangible, affectionate, and instrumental support appears to have a protective effect on the risk of postpartum depression, consistent with the literature (Beck 2001;Logsdon and Usui 2001) and our theoretical model. Qualitative data from this study revealed that women reported sources of support to include mothers, husbands or partners, and older children, but for women who lack those resources, a primary care provider inquiring about the mothers' support and helping them identify community resources may be an option.…”
Section: Discussionsupporting
confidence: 87%
“…Women's risk of postpartum depression may be influenced by multiple factors such as history of depression (Da Costa et al 2000;Horowitz et al 2005), stressful life events (Da Costa et al 2000;Robertson et al 2004), difficult infant temperament (Beck 2001;McGrath et al 2008), social support (Beck 2001;Logsdon and Usui 2001), and breastfeeding (McCoy et al 2006;Sharma and Corpse 2008). The objective of this paper is to extend previous research by longitudinally investigating the effects of total workload and other work-related factors (e.g., workplace support, job satisfaction, job flexibility) on postpartum depression in the first 6 months after childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent risk factors for PPD include antepartum depression, personal psychiatric history, family psychiatric history, poor social support, and poverty (Forty et al, 2006;Logsdon & Usui, 2001). Up to 45% of women with antepartum depression develop PPD (Josefsson, Berg, Nordin, & Sydsjo, 2001).…”
Section: Callout 1 Sleep Qualitymentioning
confidence: 99%
“…Symptoms may start as early as 2 weeks and as late as one year, but usually peak between 6 and 12 weeks postpartum. Depressive symptoms have been reported to last up to 2 years postpartum (Mayberry, Horowitz, & Declercq, 2007).The most prevalent risk factors for PPD include antepartum depression, personal psychiatric history, family psychiatric history, poor social support, and poverty (Forty et al, 2006;Logsdon & Usui, 2001). Up to 45% of women with antepartum depression develop PPD (Josefsson, Berg, Nordin, & Sydsjo, 2001).…”
mentioning
confidence: 99%
“…The feminist model of counseling asserts that empowering clients to negotiate power imbalances in their relationships leads to increased self-concept and a decrease in their symptoms. Finally, feminist counseling is well suited to working with postpartum women from culturally diverse backgrounds because it takes into account the contextual forces of socioeconomic status, race, and age in addition to gender (Amankwaa, 2003;Beck, 2002;Logsdon & Usui, 2001).…”
Section: Feminist Counseling and Ppdmentioning
confidence: 99%